Effect of alcoholic and nano-particles additives on tribological properties of diesel–palm–sesame–biodiesel blends. (November 2021) - Mujtaba, M.A.; Muk Cho, Haeng; Masjuki, H.H.; Kalam, M.A.; Farooq, M.; Soudagar, Manzoore Elahi M.; Gul, M.; Ahmed, Waqar; Afzal, Asif; Bashir, Shahid; Raju, V. Dhana; Yaqoob, Haseeb; et al.
Abstract: This study focused on evaluating the lubricity of diesel–biodiesel fuel with oxygenated alcoholic and nano-particle additives. Fuel injection system lubrication depended primarily on the fuel used in the diesel engine. Palm–sesame oil blend was used to produce biodiesel using the ultrasound-assisted technique. B30 fuel sample as a base fuel was blended with fuel additives in different proportions prior to tribological behavior analysis. The lubricity of fuel samples measured using HFRR in accordance with the standard method ASTM D6079. All tested fuels' Tribological behavior examined through worn steel balls and plates using scanning electron microscopy (SEM) to assess wear scar diameter and surface morphology. During the test run, the friction coefficient was measured directly by the HFRR tribometer system. The results exhibited that B10 (diesel) had a very poor coefficient of friction and wear scar diameter, among other tested fuels. The addition of oxygenated alcohol (ethanol) as a fuel additive in the B30 fuel sample decreased the lubricity of fuel and increased the wear and friction coefficient, among other fuel additives. B30 with DMC showed the least wear scar diameter among all tested fuels. B30 with nanoparticle TiO 2 exhibited the best results with the least wear scar diameter and lowest friction coefficient among all other fuel samples. B30+DMC demonstrated significant improvement in engine performance (BTE) and carbon emissions compared to different tested samples. B30+TiO2 also showed considerable improvement in engine characteristics.